Highly efficient pulsed power supply system with a two-stage LC generator and a step-up transformer for fast capillary discharge soft x-ray laser at shorter wavelength - Sakai, Yusuke; Takahashi, Shnsuke; Komatsu, Takanori; Song, Inho; Watanabe, Masato; Hotta, Eiki (Review of scientific instruments, 2010)
Highly efficient and compact pulsed power supply system for a capillary discharge soft x-ray laser (SXRL) has been developed. The system consists of a 2.2